Penilaian Kinerja Keuangan PT KLM Ditinjau dari Rasio Keuangan dan Common Size untuk Periode 2009-2013 - Alfaizah Alfaizah; Destia Pentiana; Damayanti Damayanti (Jurnal Ilmiah ESAI, 2019)
The purposes of this study are to (a) calculate and analyze the financial performance at PT KLM when measured by financial ratios for the 2009-2013 period, and (b) calculate and analyze financial performance at PT KLM if measured by Common Size Analysis for the 2009-2013 period. The data analysis method used in this final project report is quantitative descriptive analysis of financial statements. The analysis used in the preparation of this study is financial ratio analysis and common size analysis. Financial ratios in the form of liquidity ratios (CR and QR), solvency ratios (DAR and DER) and profitability ratios (NPM, ROA and ROE) as well as common size analysis of PT KLM's income statement and balance sheet for the 2009-2013 period. Based on the results of the research on the financial performance of PT KLM with financial ratios, the financial condition of PT KLM is still dominated by debt, causing the health of the company to be generally categorized as bad while based on a common size analysis that the average balance sheet component is volatile and the trend is unstable. In 2011, 2012 and 2013 PT KLM experienced a decrease in the percentage of its current debt, while from the common size income statement it was found that the trend of the HPP component decreased from 2009-2013 and was offset by the increase in net income each year for 5 periods.Keywords: performance, financial ratio, common size.